2015
DOI: 10.1007/s40615-015-0187-7
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Cranial Gunshot Wounds: Intent and Survival

Abstract: This study reports that there are racial disparities between assault GSW and self-inflicted GSW. However, neither race nor intent is a predictor of survival outcome. Targeted efforts are needed to reduce occurrence of cranial GSW events in order to decrease associated morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
0
16
1
Order By: Relevance
“…Despite these differences, neither age, race, nor intent was predictive of survival. Similarly, Crutcher et al 9 reported disparities in injury intent between races, but intent and race were not predictive of survival in this study either.…”
Section: Discussioncontrasting
confidence: 54%
“…Despite these differences, neither age, race, nor intent was predictive of survival. Similarly, Crutcher et al 9 reported disparities in injury intent between races, but intent and race were not predictive of survival in this study either.…”
Section: Discussioncontrasting
confidence: 54%
“…Studies investigating firearm violence report a disproportionately large majority of injuries among non-Caucasian patients, immigrants, and those in low-income areas. 5,18,19 This contributes, among many other factors, to the lower life expectancy of African Americans males compared to that of Caucasian males. 20 This effect may be explainable by differing life experiences in children of different races.…”
Section: Discussionmentioning
confidence: 99%
“…In their investigation of epidemiological characteristics and racial differences in patients with gunshot wounds, they showed that race was not a predictor of survival outcome. 8 19%) 0 (0.00%) 0 (0.00%) 0 (0.00%) 0.672 Liver disease 0 (0.00%) 0 (0.00%) 0 (0.00%) 0 (0.00%) >0.99 Lymphoma 0 (0.00%) 0 (0.00%) 0 (0.00%) 0 (0.00%) >0.99 Metastatic cancer 1 (1.19%) 0 (0.00%) 0 (0.00%) 0 (0.00%) 0.672 Neurological disorder 7 (8.33%) 1 (1.20%) 0 (0.00%) 0 (0.00%) 0.043 Obesity 3 (3.57%) 2 (2.41%) 0 (0.00%) 0 (0.00%) 0.647 Paralysis 2 (2.38%) 0 (0.00%) 0 (0.00%) 0 (0.00%) 0.376 PVD 1 (1.19%) 0 (0.00%) 0 (0.00%) 0 (0.00%) 0.672 Psychosis 13 (15.48%) 2 (2.41%) 3 (7.32%) 0 (0.00%) 0.020 Renal failure 0 (0.00%) 1 (1.20%) 0 (0.00%) 0 (0.00%) 0.665 Rheumatoid arthritis 0 (0.00%) 0 (0.00%) 0 (0.00%) 0 (0.00%) >0.99 Tumor 1 (1.19%) 0 (0.00%) 0 (0.00%) 0 (0.00%) 0.672 Peptic ulcer disease 0 (0.00%) 0 (0.00%) 0 (0.00%) 0 (0.00%) >0.99 Valvular disease 0 (0.00%) 0 (0.00%) 0 (0.00%) 0 (0.00%) >0.99 Weight loss 2 (2.38%) 0 (0.00%) 1 (2.44%) 0 (0.00%) 0.543 CHF = congestive heart failure; COPD = chronic obstructive pulmonary disease; HTN = hypertension; PVD = peripheral vascular disease. Boldface type indicates statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…4 Gunshots rank among the top 2 most common causes of penetrating cranial wounds in the United States, next to stabbings. 8 Mortality rates of gunshot wounds to the head (GWH) are extremely high, with an estimated 90% of cases being fatal. Of patients who arrive to the hospital, approximately 50% die in the emergency department.…”
mentioning
confidence: 99%